Assessing The Effects Of Product VS Country Image And Hedonic VS Utilitarian Messaging On Brand Attitude - Maria Natalia Damayanti Maer; Ruth Tarigan; Indra Pratama; Feline Gozal (Journal Of Social Science (JoSS), 2024)
This study aims to analyze the most effective strategy to obtain the most favorable brand attitude when promoting a brand. It examines the effectiveness of a product or country image, as well as the hedonistic and utilitarian message towards the brand attitude of a product. This study also includes the moderating effect of brand sustainability to observe the effect of a good or bad sustainability image on the brand attitude of a product. This study uses an experimental approach using a fictitious Swiss chocolate brand with either a hedonistic or utilitarian-focused message, followed by a display of a country or product image, as well as a sustainability report using the Chocolate Scorecard as a template. The participants are then given a set of four bipolar items before and after the sustainability report to rate the brand attitude of the product. The results show a non-significant relationship between hedonistic and utilitarian messages towards brand attitude, while it shows a significant relationship between country and product image towards brand attitude. The results also show that a sustainable label shows a similar positive impact towards brand attitude, while a non-sustainable label has a more adverse impact on product image compared to country image.